A Guide to Transgender Health : State-of-the-Art Information for Gender-Affirming People and Their Supporters /: State-of-the-Art Information for Gender-Affirming People and Their Supporters. (2019) - Ph.D., Rachel Ann Heath; Ph.D., Katie Wynne
No abstract available